2016 Smart Cities Symposium Prague (SCSP) 2016
DOI: 10.1109/scsp.2016.7501043
|View full text |Cite
|
Sign up to set email alerts
|

Flood control of the smart city Prague

Abstract: After heavy rainfall in the southern part of Germany and Czech country there is a serious risk of flooding of the river Moldau in the city of Prague. Flooding can cause many damage and victims. Prevention measures are building of removable dams and evacuation of people and animals. The raising of the water level can be predicted and a smart city has disaster plans. To train involved first responders in the execution of those plans many training hours are necessary. But to simulate realistic disasters is compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…In [ 51 ], the authors proposed the use of a serious game in the smart city of Prague, which will serve as training for the different stakeholders to react appropriately to a variety of disasters. The scenario is one in which the river Vltava, the longest river in the Czech Republic, overtops its channel’s bank and floods Prague, leading to property damage and victims.…”
Section: Padl In Citiesmentioning
confidence: 99%
“…In [ 51 ], the authors proposed the use of a serious game in the smart city of Prague, which will serve as training for the different stakeholders to react appropriately to a variety of disasters. The scenario is one in which the river Vltava, the longest river in the Czech Republic, overtops its channel’s bank and floods Prague, leading to property damage and victims.…”
Section: Padl In Citiesmentioning
confidence: 99%
“…In recent years we published some papers on the flooding MOOC on learning conferences [24][25][26][27][28], which were focusing on presenting MOOCs as a new didactical learning tool. The content of the course and especially the crisis aspects were hardly discussed.…”
Section: Related Workmentioning
confidence: 99%
“…We found that one of the difficult problems in developing a MOOC was to organize cooperation between students. This was because of the following reasons: (1) Many students prefer to study individually rather than in a group; (2) The student population participating in the MOOC is rather heterogeneous with respect to age, education, background and abilities; (3) Cooperation via social media is difficult to organize in distant learning on a large scale; and (4) Compared to regular students most students involving in MOOCs have no direct relation to each other and there is usually a great group of left-overs not participated in cooperative groups [27]. Therefore, the integration of social media and group interaction is still under development.…”
Section: Learning Module Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue generates the need for methods that aim at identifying the loopholes in emergency response plans before disasters occur. So far approaches which were introduced to deal with this problem can be categorized as follows: (a) Approaches based on stakeholder consultation and periodic drills, collaboration exercises and strategic exercises, (Perry, 2004;Berlin & Carlström, 2014;Peterson & Perry, 1999;Gwynne et al, 2020), (b) serious games approaches (Rothkrantz, 2016;Brawley, 2016), (c) computer based simulations (Chen, Zhang, Sun, & Liu, 2016;Khalil, Abdel-Aziz, Nazmy, & Salem, 2009), (d) formal modeling approaches to compare existing disaster plans (Hoogendoorn, Jonker, Popova, Sharpanskykh, & Xu, 2005),(e) a suite of tools for emergency plan management support like SAGA (Gai, Du, & Deng, 2018;Canós, Borges, Penadés, Gómez, &Llavador, 2013) and (f) content and semantic analysis methods (Jung, Song, & Park, 2017;Khalid & Yusof, 2018). This dissertation introduces a new methodology that aims at: a) identifying the emergency plans' loopholes and b) providing a numerical value that indicates what the "distance" of the emergency response plan is against a version of the plan that has addressed the identified loopholes.…”
Section: Summary In Englishmentioning
confidence: 99%